Optimizing Hospital Waste Management through Fly Trap Technology: A Cost and Potential Problem Analysis - Agistya Rizza Subagyo; Vionna Chantika Salsabilla; Irma Juliana Samantha; Muhammad Faisal Irham; Muhammad Rapika; Mega Mutiara Sari; I Wayan Koko Suryawan (Jurnal Serambi Engineering, 2023)
The problem that often occurs in hospitals is that regulations related to hospital environmental health still need to be popular in the community. However, the development of technology and science has made agricultural tools and machines experience development and renewal and adapt to environmental conditions. Many types of fly control are available, such as fly traps in temporary garbage shelters in hospitals. This study analyzes operational needs and problems encountered by implementing fly trap technology in hospitals. This study consisted of three stages: budgeting, calculating the Kepner-Tregoe Situation Appraisal (KTSA), and the Kepner-Tregoe Potential Problem Analysis (KTPPA). The total operational costs required for this tool are IDR 887,496.00. Where this cost includes the component of preventing problems that must be faced in fly trap operations. Identification of tool constraints in operation consists of damage to the net on the fly trap, garbage piling up due to overloading in the garbage container, blockage of the entry path for flies to the fly trap, and the garbage collector coming into contact with the waste at the TPS. There are four potential problems in implementing fly traps that we previously identified, where there are possible causes, preventive actions, and contingent actions that can be taken to overcome these potential problems.